PENILAIAN KINERJA PEGAWAI APARATUR SIPIL NEGARA BADAN PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN LAMPUNG TENGAH DENGAN PENDEKATAN IMPORTANCE PERFORMANCE ANALYSIS - Supomo, Supomo; Suhada, Bambang; Suharto, Suharto (Universitas Muhammadiyah Metro, 2022)
This study aims to measure the performance of State Apparatus Employees (ASN) at the Central Lampung Regional Research and Development Agency. Assessment This study only uses services as an independent variable. In this study, 27 ASNs were involved as questionnaire respondents using the census method. Data testing techniques used in this study include validity testing with factor analysis, reliability testing, gaps, and Importance and Performance Analysis (IPA). IPA is a research method by comparing the level of importance with the level of implementation. The results showed that the results of the performance appraisal integrity and integrity are not important. Based on the research results, the most important attribute is increasing the priority to be done in order to remain competitive. Meanwhile, attributes that are deemed less important do not require temporary repairs, if necessary they are ignored or eliminated.